BIAYA PROMOSI, PANGSA PASAR DAN PROFITABILITAS PERBANKAN INDONESIA TAHUN 2010-2017 - Andi Ruslan; Cepi Pahlevi; Syamsu Alam; Mursalim Nohong (Fakultas Ekonomi dan Bisnis Universitas Atma Jaya Makassar, 2019)
The purpose of this study is to obtain empirical evidence of the effect of promotional costs on market share of third party funds and bank profitability (ROA). The sample using bank that publishes financial statements in full during 2010-2017 and is included in Books 3 and 4 categories related to business activities and office networks based on bank core capital. The data analysis technique in this study is path analysis with AMOS software (Analysis of Moment Structure). The results show that promotion costs have a positive and significant effect on DPK market share, promotion costs have a positive but not significant effect on bank profitability, market share deposits have a positive and significant effect on bank profitability. Promotion costs have a positive and significant positive effect on bank profitability through DPK market share.